THE IMPACT OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. HJ BUSANA INDAH QUALITY CONTROL DIVISION SUKABUMI - Muhamad Abid; Iin Jamilah (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of work discipline and work environment on employee performance in the Quality Control Division of PT. Hj Busana Indah. The research adopts a quantitative method with an associative approach to analyze the relationships between variables. The population consists of 120 employees in the Quality Control division, and the sample size was determined using Slovin’s formula, resulting in 99 respondents selected through simple random sampling. Data were collected through surveys and analyzed using SPSS software. The findings indicate that work discipline has a significant positive effect on employee performance, while the work environment also contributes but to a lesser extent. A well-structured disciplinary system enhances productivity, and a supportive work environment fosters motivation and efficiency. Multiple regression analysis confirms that both variables play a role in improving performance. The study recommends strengthening discipline policies and enhancing workplace conditions to optimize employee performance and company competitiveness.